Blackness as permanent exile: black female flesh against the human - Mgqoboka, Othandwayo (My University, 2022)
black-Human-woman-exile. This research is an attempt at interrogating why black women have been left out of the archives of black intellectual histories. What begins as an examination of the structural codes that render black women illegible expands into thinking about the positionality of black people in the world (or rather out-the-world) and how that might have implications for questions of blackness, gender and unfreedom. It utilises a ‘Chorus’ of black women from Miriam Makeba to Sila van den Kaap, from Hortense Spillers to Saidiya Hartman to critique the project of ‘including’ of black women into the archives of black intellectual histories, by dislocating blackness from the ‘Human’ and freedom, and with it, seeking to theorise blackness differently in a way that centres the black female flesh.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Arts in Sociology at the University of the Witwatersrand, 2021